2020
DOI: 10.1097/md.0000000000022538
|View full text |Cite
|
Sign up to set email alerts
|

Abortion is associated with knee osteoarthritis among older women in China

Abstract: The current studies revealed inconsistent relationship between reproductive factors and osteoarthritis. Community-based research has not been conducted in China. The study was to examine the association of reproductive factors with the prevalence of knee osteoarthritis (OA). Through a multistage stratified random sampling method, 10 streets or villages from 5 cities in Hunan province were randomly selected, a total 2746 eligible women aged 50 to 83 were recruited in this cross-sectional study. A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, in a study conducted in 14 nulliparous and 14 multiparous patients, it was shown that the risk of osteoarthritis increased as a result of the alteration of cartilage mechanics in multiparous patients (22). In addition, a study suggested that there is a relationship between abortion and knee osteoarthritis, and that it may increase knee osteo-arthritis (23).…”
Section: Nulliparousmentioning
confidence: 99%
“…However, in a study conducted in 14 nulliparous and 14 multiparous patients, it was shown that the risk of osteoarthritis increased as a result of the alteration of cartilage mechanics in multiparous patients (22). In addition, a study suggested that there is a relationship between abortion and knee osteoarthritis, and that it may increase knee osteo-arthritis (23).…”
Section: Nulliparousmentioning
confidence: 99%
“…Therefore, this study aimed to 1) understand the prevalence of PAFPS and 2) explore the factors related to contraceptive method choice after receiving PAFPS in Hunan Province, China. The details of data collection have been reported elsewhere [27][28][29]. Data collection used four types of questionnaires in four age groups (10-19 years, 20-39 years, 40-49 years, and 50-70 years), which had undergone extensive literature research and were evaluated by an expert panel comprised of 10 experts from Central South University, an a liated hospital, and the Hunan Province Women's Federation.…”
mentioning
confidence: 99%